Resuscitative endovascular balloon occlusion of the aorta (REBOA): Comparison with immediate transfusion following massive hemorrhage in swine. Issue 6 (December 2015) - Park, Timothy S.; Batchinsky, Andriy I.; Belenkiy, Slava M.; Jordan, Bryan S.; Baker, William L.; Necsoiu, Corina N.; Aden, James K.; Dubick, Michael A.; Cancio, Leopoldo C.
Abstract : BACKGROUND: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is less invasive than emergency department thoracotomy for the treatment of massive hemorrhage. We evaluated the effects of REBOA on carotid blood flow (Qcarotid ) in a porcine model of massive hemorrhage. We hypothesized that REBOA restores Qcarotid faster than reinfusion of blood. METHODS: Spontaneously breathing sedated Sinclair pigs underwent exponential hemorrhage of 65% total blood volume in 1 hour. They were randomized into three groups. Positive control (PC, n = 7) underwent immediate transfusion of shed blood. REBOA (n = 21) received a novel 7 Fr ER-REBOA catheter (Pryor Medical, Arvada, CO) placed into aortic Zone 1 via a femoral artery introducer for 30 minutes or 60 minutes, with transfusion either after deflation or midway through inflation. Negative control (n = 7) received no resuscitation. Qcarotid was recorded continuously using an ultrasonic flow probe. Survival and time between Qcarotid, min and both a stable maximal value (Qcarotid, max ) and restoration of baseline flow (Qcarotid, new BL ) were compared by Kaplan-Meier analysis. RESULTS: Median time to Qcarotid, max was 3.0 minutes in the REBOA group versus 9.6 minutes in the control group ( p = 0.006). Median time to Qcarotid, new BL was 6.0 minutes in the REBOA group versus 20.5 minutes in the PC group ( p = 0.11). Slope of the linear regression between Qcarotid, min and Qcarotid, new BL was 16.7 in REBOA and 10.4 in PC ( p = 0.31). Four-hour survival was 95% (20 of 21) in the REBOA group versus 71% (5 of 7) in the PC group ( p = 0.06) and 0% in the negative control group. CONCLUSION: REBOA resulted in the restoration of Qcarotid ("cerebrovascular resuscitation") at least as rapidly as retransfusion of shed blood, with equivalent 4-hour survival. Further studies of REBOA, to include mitigation of end-organ effects and longer follow-up, are needed. Abstract : Supplemental digital content is available in the text.